Hubungan Antara Pola Tidur Dan Kesehatan Mental Pada Mahasiswa Kedokteran Selama Masa Studi Klinis - Br. Sebayang, Julenda Irianti (Universitas HKBP Nommensen, 2025)
Background: Sleep is an essential biological function crucial to mental health and cognitive performance. Medical students undergoing clinical rotations are often exposed to irregular schedules that impair sleep patterns. This disruption can exacerbate psychological distress and academic decline. Objective: This study aims to explore the relationship between sleep patterns and mental health among medical students during clinical rotation periods. Methods: A qualitative descriptive phenomenological approach was employed. Fifteen medical students in clinical rotations at the Faculty of Medicine, Universitas HKBP Nommensen Medan, were selected through purposive sampling. Data were collected using in-depth semi-structured interviews and analyzed using thematic analysis. Results: The majority of participants reported significant disruption in sleep duration, quality, and rhythm. Most slept less than five hours on duty days, and experienced fatigue, mood disturbances, impaired concentration, and emotional instability. Several participants developed maladaptive coping mechanisms and reported symptoms of anxiety, depersonalization, and hopelessness. Disconnection from spiritual, social, and academic life was noted. Clinical rotation demands and unsupportive institutional environments were identified as key stressors affecting sleep and mental health. Conclusion: Disturbed sleep patterns among medical students during clinical rotations are strongly associated with adverse mental health outcomes. Sleep deprivation acts as both a symptom and a contributing factor to psychological distress, calling for systemic awareness in medical education design. Keywords: sleep quality, medical students, clinical rotation, mental health, psychological distress ABSTRAK Latar Belakang: Tidur merupakan fungsi biologis penting yang berperan besar dalam menjaga kesehatan mental dan fungsi kognitif. Mahasiswa kedokteran yang menjalani rotasi klinik sering menghadapi jadwal tidak teratur yang mengganggu pola tidur, sehingga meningkatkan risiko tekanan psikologis dan penurunan akademik. Tujuan: Penelitian ini bertujuan untuk mengeksplorasi hubungan antara pola tidur dan kesehatan mental pada mahasiswa kedokteran selama masa rotasi klinik. Metode: Penelitian ini menggunakan pendekatan fenomenologi deskriptif kualitatif. Sebanyak lima belas mahasiswa klinik Fakultas Kedokteran Universitas HKBP Nommensen Medan dipilih melalui teknik purposive sampling. Pengumpulan data dilakukan melalui wawancara mendalam semi-terstruktur, kemudian dianalisis menggunakan teknik analisis tematik. Hasil: Sebagian besar partisipan mengalami gangguan signifikan pada durasi, kualitas, dan ritme tidur. Mayoritas tidur kurang dari lima jam saat jadwal jaga, serta mengalami kelelahan, gangguan emosi, kesulitan konsentrasi, dan ketidakstabilan psikologis. Beberapa mengembangkan mekanisme koping maladaptif dan menunjukkan gejala kecemasan, depersonalisasi, serta kehilangan harapan. Terdapat keterputusan dari kehidupan spiritual, sosial, dan akademik. Tuntutan rotasi klinik serta kurangnya dukungan institusional menjadi pemicu utama gangguan tidur dan kesehatan mental. Kesimpulan: Gangguan pola tidur pada mahasiswa kedokteran selama masa klinik memiliki hubungan erat dengan kemunduran kondisi kesehatan mental. Kurang tidur berfungsi ganda sebagai gejala dan faktor pemicu stres psikologis, yang menunjukkan pentingnya perhatian sistemik dalam desain pendidikan kedokteran.